Microfluidic assay for simultaneous culture of multiple cell types on surfaces or within hydrogels - Shin, Yoojin (2012)
This protocol describes a simple but robust microfluidic assay combining three-dimensional (3D) and two-dimensional (2D) cell culture. The microfluidic platform comprises hydrogel incorporating chambers between surface-accessible microchannels. Using this platform, well-defined biochemical and biophysical stimuli can be applied to multiple cell types interacting over distances of <1mm, thereby replicating many aspects of the in vivo microenvironment. Capabilities exist for time-dependent manipulation of flows and concentration gradients as well as high-resolution real-time imaging for observing spatial-temporal single cell behavior, cell-cell communication, cell-matrix interactions and cell population dynamics. These heterotypic cell type assays can be used to study cell survival, proliferation, migration, morphogenesis and differentiation under controlled conditions. Applications include the study of previously unexplored cellular interactions, and have already provided new insights into how biochemical and biophysical factors regulate interactions between populations of different cell types. It takes 3 days to fabricate the system and experiments can run for up to several weeks.